Business Registration Reforms in China : A Case Study - Wei, Wenting; Sanchez Ortega, Luis Aldo (World Bank, Washington, DC, 2022)
In the past, the business registration system in China was complicated and market access was highly restricted and regulated. The business registration process focused too much on administrative approvals for market entry and not enough on oversight of firm activities. Firms are not allowed to start operations before being registered and receiving a business license and the business license is the only document indicating a firm’s legal identity. Before the 2014 business reform initiative, firms were also legally required to obtain various registration certificates in addition to a business license. People’s Republic of China (PRC or China) has been making a great effort to simplify its business registration process, enhance its efficiency, and reduce its cost. China has reduced both the amount of time and the number of procedures required to start a business by more than two thirds within the past decade.In 2014, China launched a country-wide multi-year National Business System Reform Initiative to ease market access, making it easier to start a business by streamlining administrative procedures, while strengthening post-registration supervision by setting up the corporate social credit system. China has made remarkable progress to reform its business registration system over the past decade, cutting the number of procedures to register a business by more than two-thirds, and shortening time to register from 34 days in 2014 to 9 days in 2020.